2022
DOI: 10.1186/s12875-022-01870-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health and wellbeing of primary healthcare workers during COVID-19 pandemic in Malaysia: a longitudinal qualitative study

Abstract: Background Primary healthcare workers (PHCWs) are at the frontline of dealing with viral pandemics. They may experience significant psychological stresses, which have hitherto not been examined in depth. We aimed to explore the impact of the COVID-19 pandemic on the psychological health and wellbeing of frontline PHCWs in Malaysia. Method We purposively recruited PHCWs with diverse backgrounds in Klang Valley, Malaysia. Using longitudinal qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Qualitative data further supported this change, highlighting a more supportive and compassionate environment within the healthcare facility. These results align with Hypothesis 3, demonstrating positive changes in attitudes and perceptions, agreed with Khoo et al who found that the psychological health and wellness, as well as attitudes of primary healthcare workers (PHCWs), changed the initial phases of the pandemic, which were shaped by their perception of the risk of getting the disease and their belief systems [23].…”
supporting
confidence: 90%
“…Qualitative data further supported this change, highlighting a more supportive and compassionate environment within the healthcare facility. These results align with Hypothesis 3, demonstrating positive changes in attitudes and perceptions, agreed with Khoo et al who found that the psychological health and wellness, as well as attitudes of primary healthcare workers (PHCWs), changed the initial phases of the pandemic, which were shaped by their perception of the risk of getting the disease and their belief systems [23].…”
supporting
confidence: 90%
“…Perceived risk of COVID-19 disease has an impact on the psychological health and well-being of HCWs (Khoo et al, 2022). In the study comparing anxiety and the perception of control of the COVID-19 pandemic conducted by Ekiz et al (2020), it is determined that demographic characteristics of people create differences in the perception of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It also changed Sweden's work organization and routine in primary healthcare facilities, pushing its workers to adapt abruptly to stressful conditions [ 12 ]. In Malaysia and Spain, primary health workers feared handling COVID-19 even after years of the pandemic, initiating continuous psychological distress [ 13 , 14 ]. Even the medical liability of the population to be COVID-19 vaccinated has brought legal repercussions for healthcare workers in the European Union, increasing their stress and burnout [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even the medical liability of the population to be COVID-19 vaccinated has brought legal repercussions for healthcare workers in the European Union, increasing their stress and burnout [ 15 ]. This fear is also combined with their worries about any risk of transmitting the disease to their family members [ 14 ].…”
Section: Introductionmentioning
confidence: 99%